Simulation analysis of factors affecting air route connection in China. (January 2016) - Zhang, Yaping; Peng, Ting; Fu, Chuanyun; Cheng, Shaowu
Abstract: In order to explore the impacts of various factors on air route connection, a probability model is constructed to simulate the Chinese airline network (CAN) in 2010, and the influences of tertiary industry output, degree and the spatial distance between two navigable cities on the analog results are discussed. Our research shows that, the opening of an air route is not completely determined by the potential air passenger flow of it, although the latter is playing a leading role. In addition, the connection probability of an air route is significantly affected by the tertiary industry outputs and degrees of corresponding two navigable cities, but little influenced by the spatial distance between them. Moreover, scale economies effect obtained from the increasing of degree is apparently greater than that brought by the developing of social economy, so CAN is more inclined to evolve into a hub-and-spoke network. Highlights: The opening of an air route is not completely determined by the potential air passenger flow of it. Tertiary industry and degree significantly affect the connection probability of an air route. Chinese airline network is more inclined to evolve into a hub-and-spoke network. The spatial distance between navigable cities does not obviously affect the connection probability of an air route.